2013
DOI: 10.1186/1472-6920-13-115
|View full text |Cite
|
Sign up to set email alerts
|

Shifting perceptions: a pre-post study to assess the impact of a senior resident rotation bundle

Abstract: BackgroundExtended duty hours for residents are associated with negative consequences. Strategies to accommodate duty hour restrictions may also have unintended impacts. To eliminate extended duty hours and potentially lessen these impacts, we developed a senior resident rotation bundle that integrates a night float system, educational sessions on sleep hygiene, an electronic handover tool, and a simulation-based medical education curriculum. The aim of this study was to assess internal medicine residents’ per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Scott et al used a quasi-experimental design to study nurses working on medical -surgical units in 3 major acute care Michigan hospitals and found a decrease number of errors following fatigue training (p = 0.01) (32). Fabreau et al used a quasi-experimental design to study internal medicine residents at two large academic hospitals in Canada and found that fatigue training was associated with a decrease in the residents' perception of their potential for error (p = 0.003) (36). The pooled effect of these studies was not estimable.…”
Section: Impact Of Fatigue Education and Training On Patient Safety Omentioning
confidence: 99%
See 2 more Smart Citations
“…Scott et al used a quasi-experimental design to study nurses working on medical -surgical units in 3 major acute care Michigan hospitals and found a decrease number of errors following fatigue training (p = 0.01) (32). Fabreau et al used a quasi-experimental design to study internal medicine residents at two large academic hospitals in Canada and found that fatigue training was associated with a decrease in the residents' perception of their potential for error (p = 0.003) (36). The pooled effect of these studies was not estimable.…”
Section: Impact Of Fatigue Education and Training On Patient Safety Omentioning
confidence: 99%
“…Four quasi-experimental studies evaluated the impact of fatigue education and training interventions on diverse indicators of long-term health (e.g., selfreported mental health, physical health, and depression symptoms) (12,34,36,39). A pooled effect is not estimable given the diversity in measures and measurement timing.…”
Section: Impact Of Fatigue Education and Training On Indicators Of Lomentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27]31,32 However, in 1 of these studies, 22.6% of respondents reported there was information they did not receive at handoff that would have helped them care for patients. 26 Other studies 22,25,30,33,36,37 noted that respondents reported increased quality of handoffs with an electronic handoff system. In 1 study, residents used 3 different handoff protocols (written, electronic, and face-to-face), with reports of protocol deviations lowest in the face-to-face phase (28%), highest with written handoffs (67%), and electronic handoffs falling in the middle (50%).…”
Section: Self-reported Measuresmentioning
confidence: 99%
“…In 1 study, residents used 3 different handoff protocols (written, electronic, and face-to-face), with reports of protocol deviations lowest in the face-to-face phase (28%), highest with written handoffs (67%), and electronic handoffs falling in the middle (50%). 38 In 9 studies (24%), perception of patient safety and/or quality of care improved 22,27,31,36,39 ; better patient management 21,25 or fewer near misses 30 were reported; and there was a reduction in missed patients. 34 However, a randomized crossover study found no statistically significant differences in resident-reported unexpected events, medical errors, or adverse drug events when comparing the electronic handoff system to the standard systems used (ie, written lists, card based, or a team-developed spreadsheet), 40 and another study found no difference in reported unexpected events pre-to postimplementation of a new electronic handoff system.…”
Section: Self-reported Measuresmentioning
confidence: 99%